HUBUNGAN LUARAN SUBJECTIVE GLOBAL ASSESSMENT SGA DENGAN DERAJAT KEPARAHAN STROKE - Lisda Amalia,* Fadila Arsanti,** Ginna Megawati*** (NEURONA, 2019)
INTRODUCTION STROKE IS A CEREBROVASCULAR DISEASE CAUSED BY THE SUDDEN DEATH OF BRAIN CELLS NUTRITION PLAYS AN IMPORTANT ROLE IN STROKE INADEQUATE INTAKE OF NUTRIENTS AFFECTS SEVERITY OF STROKE SUBJECTIVE GLOBAL ASSESSMENT SGA CAN BE USED TO ASSESS THE NUTRITIONAL STATUS OF STROKE PATIENTS WHILE SEVERITY OF STROKE IS KNOWN BY ASSESSING NEUROLOGICAL DEFICITS BASED ON THE NATIONAL INSTITUTE OF HEALTH STROKE SCALE NIHSS